COVID-19 and compulsory vaccination in Brazil: initial discussions in Information Science - Vignoli, Richele Grenge [UNESP]; da Silva, Rafaela Carolina [UNESP] (My University, 2022)
Brazil is one of the biggest movements of resistance to mandatory vaccination since the Vaccine Uprising and has experienced leadership rates in the number of deaths by COVID-19. From this perspective, this study seeks to investigate, by a bibliographic search in Information Science databases and in Brazilian laws, compulsory vaccination in the context of COVID-19. The objective is to contribute to the Brazilian discussions about compulsory vaccination in relation to COVID-19, in the scope of Information Science and its subareas. The results point that Information Science can base this type of conflict, because its sub work areas lead to rethinking the meanings that knowledge receives in society. It is concluded that clarifying and guideding the population of the efficacy and need for vaccination can be an even greater challenge than overcoming the disease itself. Therefore, educating society about the legal provisions that lead to vaccination and that dispel anti-vaccine and anti-scientific discourses is a theme to be incorporated into the scope of investigation of Information Science, mainly in areas such as Knowledge Organization, Information and Knowledge Management, Information Literacy, and Information Mediation.
COVID-19 y la vacunación obligatoria en Brasil: debates iniciales en la Ciencia de la Información
COVID-19 e vacinação compulsória no Brasil: debates iniciais na Ciência da Informação
Keywords: anti-vaccination movement; Brazil; COVID-19; Information Science; obligatory vaccination